PERENCANAAN FASILITAS PARKIR SEKOLAH TINGGI TEKNOLOGI PAGAR ALAM - jeny Suwa Muda (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2019)
The problem of the need for parking facilities is a phenomenon that is common, especially in big cities as well as in the city of Pagar Alam especially public facilities centers, one of which is on campuses including STT Pagar Alam as a public facility of course also has parking facilities as a place put the end vehicle, the parking area at STT Pagar Alam as a place to park the students, employees / employees, lecturers and guests to park their vehicles with limited land, on the peak peak parking time is on Monday to Friday , the available parking lot currently is an unorganized yard or field and does not yet have a parking lot or building and parking signs causing irregularity / unity so that the visible impression is not well ordered, both the neatness and grouping of parking types, past lanes cross and tends to make students sometimes park k its vehicles are disembarang places and on the road where the access in and out of the vehicle, it is expected that this research can provide an overview of parking area planning, parking design, parking signs and parking arrangements at STT Pagar Alam.